Below the nation state: power asymmetry and jurisdictional boundaries around the archives of Madeira Archipelago - Macedo, Laureano Secundino Ascensão de, 1978- (2022)
The main purpose of this chapter is to describe a case study developed in a sub-national context between the Autonomous Region of Madeira and the National Archive ‘Torre do Tombo’ (ANTT). Our analysis will focus theoretically on the etiologies of dispossession and empirically on a case study. Thus, the main questions that will lead this case study are: ‘Why were the Madeiran fonds taken in the past to or by ANTT?’ and ‘How were these Madeiran fonds represented in finding aids provided by ANTT and the RAM?’. Finally, based on nissological critiques,13 we will define and contextualise the notion of sub-national displaced archives as an underresearched subset of disputed archival claims, in order to reveal some particular aspects of this phenomenon.